Multi-functional anodes boost the transient power and durability of proton exchange membrane fuel cells - Gurong Shen (Nature Portfolio, 2020)
Proton exchange membrane fuel cells often suffer from low lifetimes and high cost. Here, the authors enhance the transient power performance and durability of these fuel cells by integrating a thin layer of tungsten oxide within the anode, which acts as a hydrogen reservoir, oxygen scavenger, and a regulator for the hydrogen-disassociation reaction.